Requisitos de informação e mapas do processo de projeto de estruturas em concreto armado: um estudo de caso utilizando a metodologia IDM - Cristiano Eduardo Antunes; Sérgio Scheer (PARC: Pesquisa em Arquitetura e Construção, 2014)
The construction industry is facing the Building Information Modeling (BIM) paradigm and all its potential. In order to this paradigm becomes largely adopted and fully utilized, the interoperability issue must be properly addressed. While the IFC schema covers the data model necessary for data exchange, the processes occurring daily in the industry need to be better known. In this sense, this paper reports a research that explored the design process of reinforced concrete structures using BIM based systems. To reach this goal, a case study was developed in a structural design company, where the researcher collected data by participant observation, interviews and documental analysis. After the data collection and the analysis of the internal design routines and external communications during the design process, process maps were elaborated containing all the activities developed during the contracted projects. Furthermore, it was appropriately registered the information requirements for each one of the activities using the IDM (Information Delivery Manual) standards. It was possible to characterize the design process of reinforced concrete structures in the studied company when using BIM based systems, as well as to identify the stakeholder information requirements. After the processes and information flows analysis it was also possible to propose a new optimized workflow. This workflow aimed to reduce the number of analogic activities during the studied design process, as well as helped to propose new information exchanges following the IDM methodology.